2003
DOI: 10.1210/en.2002-0087
|View full text |Cite
|
Sign up to set email alerts
|

Urocortin III Is Expressed in Pancreatic β-Cells and Stimulates Insulin and Glucagon Secretion

Abstract: Urocortin (Ucn) III, or stresscopin, is a high affinity ligand for the type 2 corticotropin-releasing factor (CRFR2) receptor recently identified in rodents and human. Ucn III was initially identified as a neuropeptide expressed in discrete areas in the brain. In the present study, we demonstrate that Ucn III is expressed in pancreatic beta-cells and in a mouse beta-cell line, MIN6. Ucn III secretion from the cells was measured using a highly specific RIA, and we found that high potassium, forskolin, or high g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
102
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(113 citation statements)
references
References 56 publications
10
102
0
1
Order By: Relevance
“…The dorsomedial VMN is rich with CRF 2 receptors (Van Pett et al, 2000) and Ucn 3 terminals (Li et al, 2003), and medial parvocellular (Chalmers et al, 1995) or magnocellular PVN neurons (Van Pett et al, 2000) also reportedly express moderate CRF 2 mRNA levels. Single-unit recording studies of hypothalamic slices found that stresscopin-related peptide, structurally related to Ucn 2, alters firing rates of neurons in the VMN and PVN, supporting their functional sensitivity to CRF 2 stimulation (Davidowa and Plagemann, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dorsomedial VMN is rich with CRF 2 receptors (Van Pett et al, 2000) and Ucn 3 terminals (Li et al, 2003), and medial parvocellular (Chalmers et al, 1995) or magnocellular PVN neurons (Van Pett et al, 2000) also reportedly express moderate CRF 2 mRNA levels. Single-unit recording studies of hypothalamic slices found that stresscopin-related peptide, structurally related to Ucn 2, alters firing rates of neurons in the VMN and PVN, supporting their functional sensitivity to CRF 2 stimulation (Davidowa and Plagemann, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the VMN mediates counter-regulatory responses to hypoglycemia and energy balance responses to leptin (Jacob et al, 1997;Satoh et al, 1997;Choi et al, 1999;Dube et al, 1999;Elias et al, 2000;Borg et al, 2003). VMN CRF 2 mRNA levels are upregulated by leptin, and pancreatic beta-cell Ucn 3-CRF 2 signaling is responsive to extracellular glucose levels (Li et al, 2003), suggesting a homeostatic role for Ucn 3 in responses to short-and long-term fuel availability. Consistent with this view, Zucker fa/fa rats, food-deprived adult rats (Timofeeva and Richard, 1997) and infant rats separated from their dams (Eghbal-Ahmadi et al, 1997), all conditions of perceived energy insufficiency, show decreased VMN CRF 2 mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is expressed abundantly and exclusively in mouse beta-cells [82] (Figure 2). Recently, it was reported to be expressed relatively late in the beta-cell lineage during mouse development [55,77].…”
Section: Ucn3 As An Islet Cell Maturation Markermentioning
confidence: 99%
“…While mouse UCN3 is restricted to beta-cells [56,82], its expression in macaque (Macaca nemestrina) and human islets extends to the alpha-cell [56] (Figures 1 and 2).…”
Section: Ucn3 As An Islet Cell Maturation Markermentioning
confidence: 99%
“…Using a two part search strategy of the human DNA database, a third CRH-like peptide was identified and named stresscopin (also termed urocortin III) (15)(16)(17) (18,19), with a third gene described in the catfish (20). Both receptors consist of seven transmembrane regions coupled to adenylate cyclase via G s .…”
Section: Orthologs and Paralogsmentioning
confidence: 99%